PRINSIP-PRINSIP DAN KARAKTERSITIK HUKUM ISLAM - Irzak Yuliardy Nugroho (LP2M IAI Miftahul Ulum Pamekasan, 2021)
Islam with its legal instruments has standard standards. The principles and characteristics of Islamic law are these standards. Patented sharia law provides guidance and special footing as a form of differentiation with legal products in general. The formula of Islamic law has a standard that is both vertical and horizontal. This paper will discuss more fully about the principles and characteristics of Islamic law. The idea in this paper uses a literature review, based on several related literatures, and then constructed in a structured and orderly manner. The principles and character of Islamic law will always remain and will never change. However, in reality, it will give rise to many interpretations and heremeneutics, especially when it collides with social conditions that continue to develop. The strength of the characteristic principles of Islamic law makes Islamic legal products (fiqh) always contextual and dynamic.